About the effect of the music of European classical composers on the psyche - Rahmonova Hojibuvi Rizojon qizi (Genius Journals, 2023)
The article talks about the characteristics of European classical music, the positive impact of their works on the human psyche, the healing properties of the composers' works, and mental tranquility in music
Keywords: suite; fugue; prelude; invention